Implementasi Pembagian Alokasi Air Bersih kepada Masyarakat di Daerah Rawan Bencana Kota Tangerang Selatan - Firmansyah Firmansyah; Retnowati WD Tuti (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
The main difficulties in post-disaster are the lack of clean water availability, the residents have difficulty getting clean water, both for residents who do not want to leave their settlements, or for those who fled to other places. For example, during a flood, dug wells and pump wells submerge floodwaters in a few days, besides that in the evacuation places there are no clean water or adequate sanitation facilities. Therefore, the provision of clean water is absolutely necessary in disaster-prone areas. Provision can be done with water filtration facilities around the area or it can be a clean water tanker that can be distributed to people in need. The purpose of this study is to describe the implementation of the distribution of clean water allocation to communities in disaster prone areas as well as the supporting and inhibiting factors of such implementation. The research method is qualitative with data collection techniques from interviews, observations and documents studies. Data obtained with an interactive model based on three research focus variables namely, communication and coordination, resource support and disposition. The results showed that communication and coordination as a connecting channel between actors can foster a good disposition. Resource support has a major influence on whether or not the objectives of the allocation of clean water are to be achieved. Whereas the allocation disposition shows the implementor’s ability to respond and represent. Does not rule out the possibility of the three variables that grow factors supporting and inhibiting that can be used as consideration for overcoming problems that arise.